PERBEDAAN TINGKAT STRES IBU RUMAH TANGGA YANG BEKERJA DAN IBU RUMAH TANGGA YANG TIDAK BEKERJA DI GONDANGLEGI MALANG - Nurhayati Nurhayati (LP3M IAI Al-Qolam, 2021)
One of the problems that are easily experienced by housewives, whether working or not working, is stress. The stress experienced by housewives, both working and unemployed, of course, has different levels. The purpose of this study was to determine the stress level of housewives in Gondanglegi, Malang Regency. This study uses the T test analysis method with the help of SPSS 20 For Window. The results of this study indicate that the stress level of housewives who work as PAUD teachers in Gondanglegi District has a higher average stress level, that is higher at 101.76 compared to housewives who are not working at 94.36. Based on the results of this study, it can be concluded that there are differences in stress levels between housewives who work and housewives who do not work in Gondanglegi.